Taking table tennis vertical movement as an example to explore the combination of mechanical problems and computational simulation - Li, Hang (Journal of physics. Conference series, 2020)
With the gradual progress of systematic science, computational simulative technology has become a new subject. It can be applied in every field of daily life. Mechanics in physics has always been the focus of academic attention. In this paper, the vertical movement of table tennis is analyzed and the motion state of table tennis in the falling process is described. It gets the mathematical equation and the division equation of the movement and designs the corresponding simulative program by using the computer, so as to study the movement law of the ball. This research method can promote and improve students' interest and level in studying mechanics, mathematics and computational science. It has a far-reaching influence on the development of physics in China.